An Analysis of theWeb Accessibility of the Sites of the Brazilian Federal Universities Based on e-MAG - Santos, Anna Theresa Carlos Dos; Maia, Lucinéia Souza (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Web accessibility is important so that people, especially those with disabilities, can access and interact with the Internet. Therefore, it is necessary for Web content to be accessible to all audiences, including those of federal universities. Federal universities are public and tuition-free institutions of higher education, maintained by the Federal Government. In Brazil, there are 68 federal universities, distributed across all states and the Federal District. All universities have websites with relevant information for the academic community and civil society. Sometimes, the website is the first contact of the future student with the university. In this sense, the objective of this paper is to provide a Web accessibility scenario of the websites of Brazilian federal universities. The research was classified as quantitative and exploratory, in which evaluations were made on all websites of Brazilian federal universities with the Website Accessibility Evaluator and Simulator, in accordance to the Accessibility Model in Electronic Government. As a result, it was found that most of the Web accessibility errors identified are related to links. The problems regarding the description of the links were detected in 93% of the sites evaluated. Finally, in the sample of content management systems, it was found that the Joomla recorded the lowest average of accessibility errors, however, it is not possible to state that it offers the best support for the creation of accessible websites.